Do Parenting Plans Work? The Effect of Parenting Plans on Procedural, Family and Child Outcomes. (16th August 2018) - de Bruijn, Simon; Poortman, Anne-Rigt; van der Lippe, Tanja
ABSTRACT: The Dutch legislature obligated divorcing parents to draw up a parenting plan when they divorce because it believed such a plan to be beneficial for reducing procedural and family-related problems, and ultimately increasing child well-being. In this study, the authors evaluate the effectiveness of the parenting plan for both procedural, family and child outcomes simultaneously, using a natural experiment. They use recent survey data from the Netherlands ( n = 1, 470) and make a distinction between parents who divorced prior to the 2009 divorce law and those who divorced after its enactment. The implementation of the mandatory parenting plan encouraged more parents to document their agreements in writing. These written arrangements are found to be more comprehensive and are updated more often after the 2009 divorce law. With respect to the other procedural outcomes no difference with the situation before the change of the law is found. Findings regarding parental conflict are mixed, post-divorce tension increased after the 2009 divorce law, whereas extreme occurrences of parental conflict decreased. No differences are found in the level of parental contact. Additionally, the parenting plan is not found to affect child well-being, both directly and mediated through procedural and family outcomes. Most of these findings may be attributed to the fact that prior to the 2009 law reform many divorcing parents already made written arrangements regarding their children. Suggestions for further research regarding the parenting plan and possible other implications are discussed.